A course in language teaching : - Ur, Penny (Cambridge University Press, 1991)
This important new course provides a comprehensive basic introduction to teaching languages, for use in pre-service or early experience settings. It can be used by groups of teachers working with a trainer, or as a self-study resource. It consists of modules on key topics, arranged into sections covering: The Teaching Process, Teaching the Language, Course Content, Lessons, and Learner Differences. Modules can be used in sequence, or selectively. Each module presents practical and theoretical aspects of the topic, with tasks. Suggestions for classroom observation and practice, action research projects and further reading are included. Notes for the trainer with stimulating insights from the author's personal experience complete the course.